(untitled) (Bangladesh Journal of Medical Science, 2026)
Background The role of human papillomavirus (HPV), particularly the highrisk type 16, in the pathogenesis of oral potentially malignant disorders (OPMDs) remains a subject of considerable debate. While its oncogenic potential in oropharyngeal carcinoma is well-established, its prevalence and significance in precursor lesions of the oral cavity are less clear. Methods A case-control study was conducted on 100 participants: 60 patients with histopathologically confirmed OPMDs (20 each of OL, OSMF, and OLP) and 40 healthy individuals with normal oral mucosa as controls. Tissue biopsies were collected, and genomic DNA was extracted. PCR was performed using specific primers targeting the E6 oncogene region of HPV- 16. The amplified products were visualized via agarose gel electrophoresis. Results HPV-16 DNA was detected in 18.3% (11/60) of the OPMD cases, which was significantly higher than the 2.5% (1/40) positivity rate in the control group (p = 0.019). The highest prevalence was observed in OLP (25.0%, 5/20), followed by OL (20.0%, 4/20) and OSMF (10.0%, 2/20). A significant association was found between HPV-16 positivity and a history of tobacco chewing among OPMD patients (p = 0.038). The mean age of HPV-positive patients was slightly higher (48.7 ± 11.2 years) than HPV-negative patients (44.1 ± 10.5 years), though the difference was not statistically significant (p = 0.18). Conclusion The study demonstrates a significant presence of HPV-16 DNA in a subset of OPMDs, particularly in patients with a history of tobacco use. This finding suggests that HPV-16 may act as a potential co-carcinogen in the multistep process of oral carcinogenesis. PCR-based detection of HPV-16 could serve as a valuable molecular tool for risk stratification and may aid in the surveillance of high-risk OPMDs. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S108-S113